2017
DOI: 10.3390/sym9030030
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent RFID Indoor Localization System Using a Gaussian Filtering Based Extreme Learning Machine

Abstract: Nowadays, the increasing demands of location-based services (LBS) have spurred the rapid development of indoor positioning systems (IPS). However, the performance of IPSs is affected by the fluctuation of the measured signal. In this study, a Gaussian filtering algorithm based on an extreme learning machine (ELM) is proposed to address the problem of inaccurate indoor positioning when significant Received Signal Strength Indication (RSSI) fluctuations happen during the measurement process. The Gaussian filteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…Using the method of ranging, where the distance between two nodes is predefined, the coordinates of the device are computed using lateration or angulation approaches. Extensive researches for indoor positioning system (IPS) has focused on the machine learning approaches such as Extreme Learning Machine (ELM) [25]. In this context, [25] proposed the ELM in order to overcome the shortcomings faced by the traditional positioning methods and provide higher positioning accuracy and robustness.…”
Section: Dolphin (Distributed Objectmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the method of ranging, where the distance between two nodes is predefined, the coordinates of the device are computed using lateration or angulation approaches. Extensive researches for indoor positioning system (IPS) has focused on the machine learning approaches such as Extreme Learning Machine (ELM) [25]. In this context, [25] proposed the ELM in order to overcome the shortcomings faced by the traditional positioning methods and provide higher positioning accuracy and robustness.…”
Section: Dolphin (Distributed Objectmentioning
confidence: 99%
“…Extensive researches for indoor positioning system (IPS) has focused on the machine learning approaches such as Extreme Learning Machine (ELM) [25]. In this context, [25] proposed the ELM in order to overcome the shortcomings faced by the traditional positioning methods and provide higher positioning accuracy and robustness. The major contribution of that work consists of a Gaussian filter combined with ELM.…”
Section: Dolphin (Distributed Objectmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental results showed that the proposed hybrid system improved accuracy by reducing the average distance error, and applying genetic algorithm (GA) based optimization technique did not improve the accuracy, further. In Wang, Shi and Wu (2017), a Gaussian filtering algorithm based on an extreme learning machine (ELM) was proposed to address the problem of inaccurate indoor positioning in the midst of significant RSSI fluctuations during the measurement process. The proposed positioning system was tested in a real experimental environment, and found to achieve higher position accuracy and speedup, compared to previous algorithms.…”
Section: Related Workmentioning
confidence: 99%